Physical layer attacks on cognitive radio networks - Sura Khalid Tawfeeq; Dr.Emad Ahmed Mohammed; Dr. Razan Abdulhamed (Genius Journals, 2023)
Due to the fact that wireless communication heavily relies on spectrum utilization, the growing demand for new wireless services and how they are used is causing a shortage of spectrum.The challenging technology known as "cognitive radio" is introduced in order to effectively use the spectrum that is currently available. It is an adaptive technology that can transmission by identifying its nearby devices. With no interference to the licensed users.cognitive radio aims to increase the effectiveness of the spectrum changes. The fact that cognitive radio operates in an open network environment increases the likelihood that an attacker will attempt to interfere with the spectral medium. Security then becomes a crucial factor.In this research we examine the physical layer security concerns for cognitive radio networks. We provide a summary of a number of current physical layer security attacks in cognitive radio networks.
Keywords: Cognitive Radio Network; Physical Layer